2024
DOI: 10.1089/ast.2022.0113
|View full text |Cite
|
Sign up to set email alerts
|

Venus' Atmospheric Chemistry and Cloud Characteristics Are Compatible with Venusian Life

Abstract: Venus is Earth's sister planet, with similar mass and density but an uninhabitably hot surface, an atmosphere with a water activity 50-100 times lower than anywhere on Earths' surface, and clouds believed to be made of concentrated sulfuric acid. These features have been taken to imply that the chances of finding life on Venus are vanishingly small, with several authors describing Venus' clouds as ''uninhabitable,'' and that apparent signs of life there must therefore be abiotic, or artefactual. In this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 111 publications
(156 reference statements)
0
3
0
Order By: Relevance
“…Bains et al (2021b,c) showed that biochemical production of phosphine was not thermodynamically impossible, based on a model where an organism maintained a neutral aqueous interior while living in a sulfuric acid droplet, but did not speculate where the energy to do this might come from. Jordan et al (2022) show that some limited sulfur-based metabolic strategies either cannot provide enough energy, or would produce chemical signatures that contradict what is currently observed in Venus's atmosphere, but Bains et al (2024) show that more than enough solar energy is available for a biosphere in the clouds, and alternative photosynthetic metabolisms may not create the same anomalies in Venus's atmosphere as the metabolisms explored by Jordan et al Such an organism is therefore not ruled out by what we know of life, but nevertheless seems intuitively implausible.…”
Section: Life As a Source Of Phosphinementioning
confidence: 92%
See 1 more Smart Citation
“…Bains et al (2021b,c) showed that biochemical production of phosphine was not thermodynamically impossible, based on a model where an organism maintained a neutral aqueous interior while living in a sulfuric acid droplet, but did not speculate where the energy to do this might come from. Jordan et al (2022) show that some limited sulfur-based metabolic strategies either cannot provide enough energy, or would produce chemical signatures that contradict what is currently observed in Venus's atmosphere, but Bains et al (2024) show that more than enough solar energy is available for a biosphere in the clouds, and alternative photosynthetic metabolisms may not create the same anomalies in Venus's atmosphere as the metabolisms explored by Jordan et al Such an organism is therefore not ruled out by what we know of life, but nevertheless seems intuitively implausible.…”
Section: Life As a Source Of Phosphinementioning
confidence: 92%
“…The suggestion that the same logic could be applied to Venus has generated much heated argument, with several authors stating that Venus is uninhabitable because of the extreme aridity and acidity of its atmosphere, and hence that life could be ruled out a priori as a candidate source for phosphine (Cockell et al, 2021;Hallsworth et al, 2021). However, the potential habitability of the clouds is still debated (Bains et al, 2021a;Limaye et al, 2021a;Limaye et al, 2021b;Cleland and Rimmer, 2022;Bains et al, 2024), so we must take the habitability of Venus' cloud decks as unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Venus has a surface that is too hot for any plausible solvent and the most complex organic chemistry; hence, it is unsuitable for supporting life. Nevertheless, scientists have speculated that the perpetual cloud cover at 48 to 60 km above Venus' surface, and with temperatures matching those found at Earth's surface, might host life (see, e.g., [1][2][3][4][5][6][7][8][9]). Venus clouds, however, are composed of concentrated sulfuric acid-an aggressive solvent that destroys most of Earth life's biochemicals and is thought to be sterile to complex organic chemistry or life of any kind.…”
Section: Introductionmentioning
confidence: 99%